Thermoelastic waves in an infinite solid caused by a line heat source - Ranjit S. Dhaliwal; Samir R. Majumdar; Jun Wang (International Journal of Mathematics and Mathematical Sciences)
The generalized thermoelasticity theory recently developed by Green and Naghdi is employed to investigate thermoelastic interactions caused by a continuous line heat source in a homogeneous isotropic unbounded solid. Hankel-Laplace transform technique is used to solve the problem. Explicit expressions, for stress and temperature fields, are obtained for small time approximation. Numerical values are displayed graphically. Our results show that this theory predicts an infinite speed for heat propagation in general, and includes the second sound phenomena as a special case.